PSEUDOMONAS AERUGINOSA-INDUCED ACUTE EXOGENOUS ENDOPHTHALMITIS POST-CATARACT SURGERY (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2023)
Introduction: The Endophthalmitis Vitrectomy Study revealed that only a small percentage of endophthalmitis cases, specifically 4.1%, were caused by Gram-negative organisms, and the most frequent of these was Pseudomonas aeruginosa. Moreover, poor visual outcomes were consistently linked to this bacterium. Objective: To provide knowledge regarding Pseudomonas aeruginosa as a cause of exogenous endophthalmitis and its management. Case Illustration: A 65-year-old male was admitted to the Emergency Department due to pain and blurred vision in his left eye. These symptoms had been present for four days and occurred three days following cataract surgery. The patient's visual acuity in the affected eye was extremely poor, with no light perception, conjunctival redness, corneal edema, and posterior synechia of the iris. A Bmode ocular ultrasound detected an abnormal echo in the left eyeball and moderate vitreous opacity, which suggested that the patient had endophthalmitis. The patient underwent emergency surgery immediately, including Pars plana vitrectomy (PPV), Silicon oil, IOL extraction, and intravitreal antibiotics injection. The vitreous was also tested with a smear test and culture, which revealed the presence of Pseudomonas aeruginosa. On the first day after the surgery, the patient's vision improved to light perception but with incorrect projection. A Fundus exam showed an attached retina with silicon oil and no macular edema. After one month, the patient's visual acuity improved to 2/60. Conclusions: Identifying the causative organisms in infectious endophthalmitis is critical in determining treatment and visual results. Pars Plana Vitrectomy (PPV) followed by intravitreal injection of antibiotics as the "gold standard" treatment for acute postoperative endophthalmitis.